1968
DOI: 10.1084/jem.127.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Hapten Carrier Relationships in the DNP-Pll·foreign Albumin Complex System: Induction of Tolerance and Stimulation of Cells in Vitro

Abstract: The ability of guinea pigs to recognize poly-I,-lysine (PLL), and hapten conjugates of PLL (H-PLL) as antigens is under the control of a single autosomal dominant gene which we will refer to as the PLL gene (1-3). Responder animals carrying this gene form specific antihapten antibodies and display delayed hypersensitivity reactions after immunization with H-PLL conjugates such as 2,4-dinitrophenyl-PLL (DNP-PLL); guinea pigs lacking the PLL gene are incapable of an immune response to DNP-PLL but can nevertheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1968
1968
1974
1974

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…In both the LDH system and the DNP-PLL-BSA system it could be shown that the induction of tolerance to the carrier led to a reduced response to a subsequent injection of carrier-hapten complex (7,12,19). In this situation the reduction of the response was quantitatively similar for both antihapten and anti-carrier antibodies (7,12).…”
Section: Resultsmentioning
confidence: 56%
“…In both the LDH system and the DNP-PLL-BSA system it could be shown that the induction of tolerance to the carrier led to a reduced response to a subsequent injection of carrier-hapten complex (7,12,19). In this situation the reduction of the response was quantitatively similar for both antihapten and anti-carrier antibodies (7,12).…”
Section: Resultsmentioning
confidence: 56%
“…The in vitro responses of lymph node ceils from such animals did not regularly reach the levels previously observed in responder guinea pigs (20). The lymph nodes of irradiated animals were small and may not have been ideal sources of immunocompetent ceils.…”
Section: Tra~f~ Of Responsiveness To Dnp-pll To Lethally Irrad~t~ Rarmentioning
confidence: 81%
“…The immune response elicited by DNP-PLL in most irradiated nonresponder recipients after the transfer of bone marrow cells from animals with the PLL gene was characterized by delayed hypersensitivity and other evidence of cellular immunity to DNP-PLL, as well as by the synthesis of significant levels of anti-DNP antibodies. Although positively charged DNP-PLL can behave as a hapten in nonresponder guinea pigs, and elicit the formation of anti-DNP antibodies when associated with a variety of immunogenic carriers (14,15), DNP-PLL has never been able to elicit delayed sensitivity in either Hartley strain or strain 13 nonresponder guinea pigs, nor has it been able to stimulate the proliferation of their lymph node cells in vitro (14,15,20). These experiments therefore establish conclusively that the ability to recognize hapten-PLL conjugates as antigens can be transferred to guinea pigs lacking the PLL gene, and that the process controlled by this gene finds expression in bone marrow derived cells.…”
Section: Discussionmentioning
confidence: 99%
“…In guinea pigs, antigen induced secondary in vitro lymphocyte transformation appears to be primarily a T-cell dependent function (23). In the mouse, this reaction is highly sensitive to anti-Thy-l.2 plus complement.…”
mentioning
confidence: 96%